The influence of traumatic brain injury on the allocation of vertical spatial attention. Issue 1 (2nd January 2020) - Hromas, Gabrielle; Polejaeva, Elena; Sozda, Christopher N.; Heilman, Kenneth M.; Schmalfuss, Ilona M.; Perlstein, William M.
ABSTRACT: Objective : Research on impairments of spatial attention has primarily investigated hemispatial neglect in brain-lesioned patients, revealing decrements in the allocation of attention to right versus left egocentric or allocentric hemispace. Whereas head trauma might injure those parts of the brain that allocate vertical attention, little is known about the influence of trauma on the allocation of visuospatial attention in vertical space. Thus, the goal of this study was to learn if chronic moderate-to-severe traumatic brain injury (m/sTBI) alters the allocation of vertical visuospatial attention as assessed by the Attention Network Task (ANT). The ANT assesses the influence of Posner-type spatial cues and distractors using an Eriksen flanker task. Methods : 12 chronic m/sTBI patients and 12 demographically-matched neurologically-healthy controls (HCs) completed a version of the ANT wherein trials were coded for cue and target locations above and below central visual fixation. Trial-wise reaction times (RT) and accuracy were subjected to mixed-model ANOVAs and planned contrasts. Results : These data were subject to secondary analyses, which revealed that across groups, median RTs were significantly faster when targets occurred above than below the central visual fixation ( p < .01); however, only HCs' error rates differed as a function of target altitude. Unlike controls, m/sTBI survivors did not exhibit the anticipated upward error-rate attentional bias. Conclusions : As alteration of spatial attention can be a major cause of disability, present findings suggest that m/sTBI survivors exhibit this loss of normal upward attentional bias. Future studies are need to learn if these patients might benefit from treatment.